The Effectiveness of Metacognitive Therapy on Dysfunctionalities in Women with Premenstrual Dysphoric Disorder - Derakhshan Roudsari, Houri (Applied Family Therapy Journal (AFTJ), 2024)
Objective: The aim of this study was to evaluate the effectiveness of metacognitive therapy on dysfunctions in women suffering from premenstrual dysphoric disorder.Method: This quasi-experimental research used a pre-test, post-test, and follow-up design with a control group. The population consisted of female dentistry students at the Islamic Azad University diagnosed with premenstrual dysphoric disorder in 2022. A sample of 30 women was selected through convenience sampling. The experimental group received metacognitive training over 12 sessions lasting 60 minutes each week, while the control group was placed on a waiting list. Data were collected using the Weisman and Beck Dysfunctional Attitude Scale (1987) and analyzed using repeated measures ANOVA through SPSS software.Findings: Results indicated that metacognitive therapy was effective in reducing dysfunctions. The eta-squared statistic also suggested that approximately 24.3% of the reduction in dysfunctions was attributable to the effectiveness of metacognitive therapy.Conclusions: Metacognitive therapy can be deemed effective in treating dysfunctions in women with premenstrual dysphoric disorder and can be used to alleviate psychological problems in these patients.